Kebangkitan Kristus Sebagai Dasar Teologis bagi Kebangkitan Orang Mati: Sebuah Analisis Biblika atas 1 Korintus 15:13 - Andris Kiamani; Ajais Yalisu (Jurnal Ilmiah Tafsir Alkitab, 2025)
The resurrection of Christ marks an important transition from despair to full expectation of the resurrection of the dead in the Christian faith. However, contemporary theology often views this resurrection as a myth, hallucination, or psychological experience, ignoring its historical basis. So this study aims to analyze the resurrection of Christ biblically to strengthen Christian faith, respond to reductive views, affirm the resurrection of Christ as the foundation of eschatological faith. In this case the author uses the method of biblical interpretation as described by Saparman, namely: exegesis to explore the meaning of the text, hermeneutics to explain the interpretation, and exposition to communicate the meaning of Christ's resurrection theologically. The results of this study confirm that the resurrection of Christ has a strong historical basis, proof of victory over death, and the foundation of faith in the resurrection of the dead. The implication of this research leads to the need for a full and deep theological understanding so that the resurrection of Christ remains the center of faith and hope of the church today.